The Effect of Plant-Based and Mycoprotein-Based Meat Substitute Consumption on Cardiometabolic Risk Factors: A Systematic Review and Meta-Analysis of Controlled Intervention Trials - Joshua Gibbs; Gah-Kai Leung (Dietetics, 2023)
Background: Climate change is a serious threat to human wellbeing and development. Global reduction of meat intake is key to addressing climate change and other modern sustainability challenges. Plant-based and mycoprotein-based meat substitutes are predicted to play a key role in the reduction of meat intake; however, their impact on human health is unclear. The main objective of this meta-analysis was to assess the short-term effects of meat substitutes on important cardiometabolic biomarkers (total cholesterol, TC; LDL-cholesterol, LDL-C; HDL-cholesterol, HDL-C; triglycerides, TG; systolic blood pressure, SBP; diastolic blood pressure, DBP; fasting blood glucose, FBG; weight) in controlled clinical trials. Methods: Embase and MEDLINE were searched to identify controlled clinical trials with meat substitute interventions and cardiometabolic biomarker outcomes. Standardised mean differences in TC, LDL-C, HDL-C, TG, FBG, SBP, DBP, and weight and 95% confidence intervals were pooled using a random effects model. Risk of bias, heterogeneity, sensitivity, and publication bias were assessed. Of the 934 records identified, 12 studies met the inclusion criteria. In the pooled analyses, the consumption of meat substitutes was associated with significantly lower TC (−0.50 mmol/L [95% CIs −0.70, −0.29]), LDL-C (−0.39 mmol/L [−0.57, −0.21]), and TG (−0.15 mmol/L [−0.29, −0.01]), non-significantly lower FBG (−0.08 [−0.23, 0.08]), SBP (−0.32 [−1.79, 1.41]), and weight (−0.12 [−1.52, 1.27]), and non-significantly higher HDL-C (0.01 [−0.02, 0.05]) and DBP (0.49 [−0.30, 1.28]). There was evidence of publication bias, and some heterogeneity was detected. The certainty of evidence was moderate for the TC and HDL-C results, low for the LDL-C, TG, SBP, DBP, and weight results, and very low for the FBG results. Conclusions: Replacement of some or all meat with plant-based or mycoprotein-based substitutes may lower TC, LDL-C, and TG.